The Formation of the Administrative-Territorial System in the Context of the Formation of Modern Ethnogeographical Systems in Bulgaria - Todorov, Vyacheslav (Journal of Danubian Studies and Research, 2024)
The purpose of the article is to identify the peculiarities of formation of the modern administrative-territorial structure of Bulgaria and to analyze their compliance with the ethnogenetic factor of the territory’s development. Resettlement has its genetic basis, its roots in the natural and geographical environment, ethno-cultural, socio-economic and political features of the territory. The genesis of settlement covers the time of initial settlement and economic development of the territory, as well as all its subsequent changes and transformations. This is one of the main types of sociogeographical processes that has its own dynamics, development trends, ethno-demographic and socioeconomic “trajectory”. The genetic taxonomy should comprehensively take into account the entire set of historical and geographical preconditions and factors of settlement, on the one hand, and the peculiarities of the settlement process itself with its dynamics, transformations and changes, on the other. This is a very complex task that requires in-depth methodological and methodological developments. The paper uses statistical and research materials. The second important component of settlement is the network of settlements (settlement network). The methodological scheme for analyzing settlement networks has been developed in great detail in social and geographical studies and is represented by numerous developments. In the context of this work, it is necessary to identify the main typological characteristics of the settlement network that determine the genetic types of settlement. The territorial organization of the population of a certain territory has the following typological features: a genetically related network of settlements has a characteristic functional and settlement structure with a certain list of functional and genetic types of settlements, their quantitative ratio and hierarchy, with more or less pronounced central locations and regional centers; a genetically related settlement network has a peculiar set of settlement locations and their evolutionary change associated with the development of the network; the network of settlements has its own territorial structure with a typical configuration, density and population of settlements, forms of their placement - single, group, agglomerated, area; the combination of such characteristics represents the territorial structure of the network of settlements. The question of correspondence between administrative- territorial systems of settlement, on the one hand, and genetic types of settlement, on the other, remains open. In a general sense, there will be no such correspondence: each of the administrative systems of settlement can, in principle, have a particular combination of genetic types of settlement and vice versa.